El Papel de las Tecnologías de la Información en la Coordinación de Transacciones - Díaz Martínez, Zuleyka; Fernández Menéndez, José; Almodóvar Martínez, Paloma (Cuadernos de Estudios Empresariales, 2004)
In this paper we develope a theoretical framework about the use of the Information Technologies in the coordination of the transactions between firms. Information Technologies allow to automatize this kind of task which leads to an enhanced efficiency. We use some results from the field of Operations Management to show how this higher efficiency has side effects: a lower flexibility in the automated tasks. Automation shows useful if we have a great number of tasks that are easy to describe and have little variety. Otherwise a «handmade» execution is adequate.
Keywords: Transactions; Coordination; Information Technologies; Production Process